Evaluation of urinary chloride dipsticks for the rapid estimation of hydration status in patients receiving artificial nutrition: Feasibility study. (April 2021) - James, S.; Tyrrell-Price, J.; Atkinson, C.; Hunt, L.; Searle, A.; Phillips, K.; Penfold, C.; Carter, J.; Ness, A.
Summary: Background and aims: The home parenteral nutrition (HPN) population face many challenges, especially with respect to fluid balance management. A low urinary sodium concentration of <20 mmol/L is commonly used as an indicator of dehydration that requires clinical assessment in these patients. The Quantab titrator dipstick measures chloride concentration of a solution and correlates with sodium concentration. We assessed whether it would be feasible to use the Quantab dipstick in the HPN population and explored relationships between Quantab dipstick estimated chloride concentration and quality of life (QOL). Methods: Patients on HPN were asked to collect urine samples at 5 specific times points (day 0, 7, 14, 21 and 28) to send to the laboratory for formal electrolyte analysis. The participant and a member of laboratory staff tested these samples with the Quantab dipstick to estimate urinary chloride concentration. Participants were instructed to complete a QOL questionnaire at each of the 5 time-points in addition to a baseline demographic questionnaire and an end-of-study questionnaire. Six participants completed an interview at the end of the study period. The relationship between participant-derived and laboratory-derived data was assessed using rank correlation coefficients. QOL assessment was correlated with urine dipstick measurements. Results: 10 patients on HPN completed the study. Data on chloride concentration as estimated by the dipstick (assessed by participants and by the laboratory) and sodium concentration from the laboratory were available for 47 urine samples. There was a positive relationship between participant dipstick estimated chloride concentration and laboratory sodium (Kendall's τ = 0.45; P < 0.001; Spearman's rs = 0.58 P < 0.001; 47 pairs). There was a strong correlation between chloride concentrations estimated by dipstick in the laboratory and by participants (Kendall 0.58 p < 0.001, Spearman's 0.69 p < 0.001; 47 pairs). In exploratory analyses, there was no relationship between QOL and dipstick estimated chloride concentration. Participants had no issues collecting urine samples but some difficulties were reported with determining the dipstick reading. Conclusions: Patients on HPN are able to collect urine specimens, complete QOL questionnaires, and are capable of using the Quantab dipstick to estimate urinary chloride concentration. The Quantab dipstick correlates with laboratory measured sodium and chloride concentrations. Further work is required to fully establish whether this point-of-care test could be used to guide fluid balance management in the HPN population.